Relationship between Information and Communication Technology and competitiveness in the tourism industry: A mapping review - Villa Espinosa, Diego Mauricio; Miñana Terol, José Luis; González-Ladrón-de-Guevara, Fernando Raimundo (RITUR - Revista Iberoamericana de Turismo, 2018)
The main goal of this study is to review several previously published papers about the relationship between Information and Communication Technology and competitiveness in the tourism industry, to determine trends, research approaches and contextualization of former studies. Ninety papers were selected from the most visited journal databases of scientist papers related to tourism and technology: ScienceDirect, Scopus, Web of Science, ProQuest, EBSCO, DOAJ, and Emerald. Once applied the Systematic Mapping Review methodology, it was found that there are four major categories in which the relationship between the constructs can be grouped competitiveness and Information and Communication Technology; direct positive relationship, negative relationship, no relationship and positive relationship through other factors. Currently, there is consensus between researchers and professionals about the positive relationship between Information and Communication Technology and competitiveness on the tourism industry from the macroeconomic point of view. However, at a microeconomic level, the discussion has not yet been resolved since the adoption of technology or any other type of resource can generate dissimilar results in different companies given the characteristics of each firm. Future lines of research should focus on determining what the factors are, and under what conditions the digitalization of firms translates into improvements in their productivity and competitiveness.